2017
DOI: 10.1001/jamaoncol.2016.3160
|View full text |Cite
|
Sign up to set email alerts
|

Association of Minimal Residual Disease With Superior Survival Outcomes in Patients With Multiple Myeloma

Abstract: Importance Numerous studies have evaluated the prognostic value of minimal residual disease (MRD) in multiple myeloma (MM). Most studies were small and varied in terms of patient population, treatment, and MRD assessment methods. Objective To evaluate the utility of MRD detection in patients with newly diagnosed MM. Data Sources A Medline search was conducted for articles published in English between January 1990 and January 2016. Study Selection Eligible studies reported MRD status and progression-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
343
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 423 publications
(374 citation statements)
references
References 44 publications
(240 reference statements)
10
343
0
7
Order By: Relevance
“…This has been important because newer therapies have achieved higher response rates that in many instances have been “deeper” in nature. 2 With the importance of MRD as a marker of long-term clinical benefit established by two independent groups 3,4 the International Myeloma Working Group (IMWG) recently revised the MM response criteria by adding “MRD negativity” as a deeper and more stringent response than stringent complete response. 5 These advances have contributed to the longer overall survival (OS) of patients diagnosed with MM in the past decade and an expectation of further improvement in the coming decade with rapid approval of drugs by the US Food and Drug administration (FDA) and the European Medicines Agency (EMA).…”
Section: Introductionmentioning
confidence: 99%
“…This has been important because newer therapies have achieved higher response rates that in many instances have been “deeper” in nature. 2 With the importance of MRD as a marker of long-term clinical benefit established by two independent groups 3,4 the International Myeloma Working Group (IMWG) recently revised the MM response criteria by adding “MRD negativity” as a deeper and more stringent response than stringent complete response. 5 These advances have contributed to the longer overall survival (OS) of patients diagnosed with MM in the past decade and an expectation of further improvement in the coming decade with rapid approval of drugs by the US Food and Drug administration (FDA) and the European Medicines Agency (EMA).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent data show that minimal residual disease (MRD)-negative status has a favorable prognostic impact, and it is known that frontline ASCT is associated with the higher rate of MRD negativity. 7,9 Based on response rates, depth of response, and PFS as surrogate markers for outcome, 3-drug combinations, including bortezomib and dexamethasone, are currently the standard of care as induction therapy prior to ASCT, but only limited data from prospective phase III trials are available to demonstrate that one combination is superior to the other. 1,4,10,11 Four to six courses of induction are recommended before proceeding to stem cell collection.…”
Section: Comments On Patientmentioning
confidence: 99%
“…2 A recent metaanalysis has confirmed that MRD-negative disease status is associated with prolonged survival. 18 Should MRD negativity not be the standard end point of MM therapy?…”
Section: Response Evaluation In MMmentioning
confidence: 99%